Space–time variability of citrus leprosis as strategic planning for crop management - Andrade, Daniel J [UNESP]; Lorençon, José R [UNESP]; Siqueira, Diego S [UNESP]; Novelli, Valdenice M; Bassanezi, Renato B (Wiley, 2018)
BACKGROUND: Citrus leprosis is the most important viral disease of citrus. Knowledge of its spatiotemporal structure is fundamental to a representative sampling plan focused on the disease control approach. Such a well-crafted sampling design helps to reduce pesticide use in agriculture to control pests and diseases. RESULTS: Despite the use of acaricides to control citrus leprosis vector (Brevipalpus spp.) populations, the disease has spread rapidly through experimental areas. Citrus leprosis has an aggregate spatial distribution, with high dependence among symptomatic plants. Temporal variation in disease incidence increased among symptomatic plants by 4% per month. CONCLUSIONS: Use of acaricides alone to control the vector of leprosis is insufficient to avoid its incidence in healthy plants. Preliminary investigation into the time and space variation in the incidence of the disease is fundamental to select a sampling plan and determine effective strategies for disease management. © 2018 Society of Chemical Industry.
Keywords: Brevipalpus spp; Citrus leprosis virus – CiLV; Citrus sinensis; epidemiology; geostatistics